Dual function ferroresonance and fault current limiter based on DC reactor. Issue 9 (1st June 2016) - Radmanesh, Hamid; Heidary, Amir; Fathi, Seyed Hamid; Babamalek Gharehpetian, Gevork
Abstract : This study presents a novel DC reactor‐based ferroresonance and fault current limiter (DRFFCL) for stabilising ferroresonance oscillations of potential transformer (PT) in 33 kV distribution network and decreasing the amplitude of the fault current to an acceptable level. At first, the ferroresonance overvoltage is introduced and various types of overvoltage in the PT are studied. Then, the effects of the suggested DRFFCL on these oscillations are investigated. It is shown that the proposed DRFFCL not only can control the ferroresonance oscillations, but also can decrease the fault current amplitude in the case of short‐circuit faults occurrence. The DRFFCL performance is simulated using MATLAB software and a scaled‐down laboratory prototype is implemented and tested for the simulation results validation. The measured results are in agreement with the simulation results and clearly show the ability of the DRFFCL for controlling both the ferroresonance overvoltage and fault current.